2019
DOI: 10.1177/1178223419879429
|View full text |Cite
|
Sign up to set email alerts
|

Pertuzumab and Trastuzumab Emtansine for Human Epidermal Growth Factor Receptor-2–Positive Metastatic Breast Cancer: Contemporary Population-Based Outcomes

Abstract: Background: Real-world outcomes for patients with human epidermal growth factor receptor-2 (HER2)-positive metastatic breast cancer (MBC) treated with pertuzumab in combination with taxane chemotherapy plus trastuzumab (TaxTP) in the first line setting and trastuzumab emtansine (TE) in any line of treatment are lacking. Methods: Cohorts of patients treated with (1) TaxTP and (2) TE from January 1, 2013 through December 31, 2016 were retrospectively obtained from a population-based database. Cohorts were descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…The proportion of our cohort with previous (neo)adjuvant treatment with trastuzumab (48%) was also similar to that reported in other observational studies [ [19] , [20] , [21] ]. The high proportion of patients treated with first-line T-DM1 who received (neo)adjuvant trastuzumab in our cohort (81%) likely reflects Australian prescribing restrictions for T-DM1 that require patients to relapse on or within 6 months of completing adjuvant trastuzumab in order to access first-line T-DM1, and overall, T-DM1 appears to have been used largely within Australian prescribing restrictions [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The proportion of our cohort with previous (neo)adjuvant treatment with trastuzumab (48%) was also similar to that reported in other observational studies [ [19] , [20] , [21] ]. The high proportion of patients treated with first-line T-DM1 who received (neo)adjuvant trastuzumab in our cohort (81%) likely reflects Australian prescribing restrictions for T-DM1 that require patients to relapse on or within 6 months of completing adjuvant trastuzumab in order to access first-line T-DM1, and overall, T-DM1 appears to have been used largely within Australian prescribing restrictions [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
“…The recent Canadian studies have reported similar OS estimates (15.4 months and 19.0 months) from their real-world cohorts to ours (18.9 months) [18,19]. Both of these studies also reported worse OS outcomes for patients who received T-DM1 following treatment with pertuzumab [18,19]. More research from patients treated in routine clinical care is needed to better understand the impact of prior pertuzumab treatment on the outcomes observed with T-DM1 therapy, but our OS estimate for second-line T-DM1 patients was more similar to that from the third-and laterline T-DM1-treated patients enrolled in the TH3RESA study (final estimate: 23 months) [28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Some studies seem to suggest lower efficacy of T-DM1 following the triplet. A recent Canadian study [23] report on 104 patients treated with T-DM1 at any line. Event Free Survival was significantly longer in the pertuzumab-naïve group compared with pertuzumab exposed group (median time to treatment failure [TTF] = 18.7 vs 5.5 months; p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous real-world studies of T-DM1 have reported absolute estimates of effectiveness in HER2+ mBC patients treated with T-DM1 and have provided comparisons of T-DM1 effectiveness between T-DM1 patients treated with different prior treatment regimens or with differing severity of disease [4][5][6][7][8][9], our study provides estimates of absolute effectiveness of T-DM1 in a larger cohort of second-line mBC patients than observed in any of these studies. Further, while these studies focused on absolute effectiveness, to our knowledge ours is the first to report on the real-world effectiveness of T-DM1 in second-line mBC relative to an alternative treatment option in this setting.…”
Section: Discussionmentioning
confidence: 85%